The Analysis of Toxicity and Safety of Nano Particles Applied in Sunscreen - Zuo, Daolin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Nano particles (NPs) with size from 1 to 100nm had been developed fast from 1950s. They are highly stable, hydrophilic and biocompatible. These NPs possess transparency and UV-absorbing properties, making them effective as protective filters. Different kinds of NPs had been applied in sunscreen. However, due to the size of metal NPs, they can easily pass-through human skin. After that, these NPs could enter the organs and the circulation system in human body. For the biochemical reactions with nano-catalysts, the adsorption and the whole reaction rate could be increased greatly due to the high ratio of surface area to volume of NPs. The evaluation of the safety of NPs is still essential to prevent any potential issues. They could cause damage to the skin or even organs in human body. The toxicity and safety of NPs including Ag, TiO2, ZnO and other ingredients are analysed, and further research are needed to be carried out to modify the recipe of sunscreen.